Phase transformation and structural properties in heat-treated Cu-12.4Al-2.5Fe-1Zr high-temperature shape memory alloys - Yildiz, Koksal (Springer Heidelberg, 2023)
This work presents effects of heat treatments at 300 degrees C, 400 degrees C and 500 degrees C for 1 h on structural/microstructural properties, transformation temperatures and some thermodynamic parameters of a Cu-12.4Al-2.5Fe-1Zr (wt%) HTSMA via XRD, SEM/EDX and DSC. Microstructure of the alloy contains 18R and 2H martensite phases, Cu9Al4 precipitates and voids. The results reveal that orientations of the 18R martensite, degree of long-range order, fractions of the Cu9Al4 precipitates, transformation temperatures and energies required for martensite nucleation and stored during martensitic transformation of the alloy change depending on the heat treatment temperature. As the heat treatment temperature raises up to 500 degrees C, both there have been shifts in the transformation temperatures of the alloy and energies required for transformations altered. Therefore, it is observed that the transformation hysteresis of the alloy increased to 111.95 degrees C and whereas the elastic energy stored during cooling decreases, the driving force required for the nucleation of the martensite phase at M-s increases.
Keywords: Cu-based HTSMA; Heat treatment; Martensitic transformation; Thermodynamic